Comparison of 10% Sucrose Fixative and 10% NBF Fixative on Hepatic Histology of Mice Using He Staining at Variable Duration - Gabriella Jihan Fatma; Juliana Cristyaningsih; Ratno Tri Utomo; Evy Dyah Woelansari (International Journal of Advanced Health Science and Technology, 2026)
NBF 10% is the most commonly used fixation solution in histopathological examinations, because this solution can maintain tissue quality as its initial state. The results of preparations from tissues fixed using 10% NBF have good quality when microscopic observation is carried out. However, routine exposure to NBF can have negative effects such as eye, nose, and throat disorders, NBF is also carcinogenic as stated by the Occupational Safety and Health Administration (OSHA). So, it is necessary to need an alternative to 10% NBF as a fixation substance to minimize the adverse effects. Based on research that has been done, it can be stated that natural sweeteners have the potential to be an alternative fixation solution. This study aims to evaluate 10% sucrose as an alternative to 10% NBF for hepatic tissue fixation. Histological quality was assessed based on the staining of the cell nucleus, cytoplasm and uniform color in the preparation. The type of research used was experimental. This research was conducted at the Farma Veterinary Center as a validation site and test animal provider, the Cytohistotechnology Laboratory of the Department of Medical Laboratory Technology as a research site, and the Faculty of Veterinary Medicine Unair as a place for excision of mice. The test material used was mice hepar with 6 replications per treatment group. After observation, the data were processed using Kruskall-Wallis and Mann-Whitney in the 10% sucrose group for 12 hours and 24 hours showed comparable results with 10% NBF for 24 hours because based on the mann whitney test, the value was obtained (p>0.05). At 10% sucrose for 6 hours showed results that were not comparable to 10% NBF for 24 hours because the man whitney test obtained a value of (p <0.05). So that 10% sucrose shows its potential as a safer alternative.